Microstructure, texture and mechanical properties of 5A02 aluminum alloy tubes under electromagnetic bulging. (5th October 2015) - Jiang, Hua-wen; Li, Ning; Xu, Zhu; Fan, Zhi-song; Yu, Hai-ping; Liu, Lin
Graphical abstract: Highlights: Dislocation structures of 5A02 Al alloy are affected by high strain rate and solute atoms. Stress state, strain rate and cross-slip activity affect the texture evolution of Al alloy. Strain strengthen of Al alloy is due to the formation of dense dislocation bands/walls. Abstract: The microstructure, texture and mechanical properties of annealed 5A02 Al alloy tubes after electromagnetic bulging have been systematically studied using transmission electron microscopy (TEM), electron backscattered diffraction (EBSD) and uniaxial tensile test. Microstructural characterizations showed that the formation of dense dislocation bands and dislocation walls in the bulged samples is due to the effect of high strain rate of electromagnetic forming and solute–dislocation interactions in the Al alloy. The texture examination revealed that the volume fraction of α-fiber texture increases after deformation, while the brass texture component in β-fiber increases, and the copper and S texture components decrease with increasing strain, indicating the occurrence of texture rotation from the initial state to a more stable orientation. In addition, the lack of cross-slip activity and high strain rate accompanied by the electromagnetic deformation in the studied Al alloy also play a role in the texture evolutions. Finally, mechanical properties of the post-bulged samples were examined by uniaxial tensile test, which shows a significant increase in yield strength and fracture strength, but decrease in fracture elongation. The enhancement of strength was discussed on the basis of the dislocation boundary strengthening mechanism, which was in good agreement with the experimental results.